Emotion ability - practices of affective citizenship in the work rehabilitation process. Issue 1 (2nd January 2020) - Wilińska, Monika; Bűlow, Pia H.
ABSTRACT: This article introduces the concept of emotion ability to illuminate the process whereby institutional meetings become an arena for testing, evoking, and regulating emotions that are deemed necessary to meet institutional goals. It focuses on the relationships and practices that are collaboratively constructed by welfare workers and clients when they interact within the context of institutional meetings. Based on an interactional analysis of a multi-party meeting, this article demonstrates the ways in which clients' ability to read, interpret, and follow specific feeling rules becomes the focal point of attention. Using video recordings, we illustrate that this process is highly collaborative, and it involves both language and body. The ability to act in accordance with the expected and required 'right feelings' emergent in the institutional encounter is, thus, a result of highly interactive processes. We discuss the concept of emotion ability as a concrete micro-level mechanism through, which practices of affective citizenship are realized in the context of institutional interactions.